2015
DOI: 10.1080/22243682.2015.1078742
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine yttria nanoparticles: synthesis and characterization

Abstract: Yttrium oxide nanoparticles (Y 2 O 3 ) have been synthesized by a low temperature co-precipitation method. The precursor material used in this research was yttrium nitrate hexahydrate (as a basic material), ammonium hydroxide (as a precipitating agent) without surfactant. The resultant precipitate Y(OH) 3 was washed with deionized water several times and then heat treated at 450 °C for 1hr. The prepared Y 2 O 3 nanoparticles were characterized by TG-DTA, XRD, DLS, Zetasizer and TEM. From the results obtained, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Ultrafine YNPs were synthesized as previously described (Kassem et al 2015). After that, surface functionalization was performed by silanizing YNPs with 3-trimethoxysilylpropyl methacrylate and grafting an ethylene glycol methacrylate phosphate (EGMP) co-polymer, as described in Sayour et al (2019) in addition to N-Fluorescein Acrylamide which was added in polymerization mixture as fluorescent monomer (Tan et al 1992).…”
Section: Synthesis Of Functionalized Core-shell Yttrium Oxide Nanopar...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrafine YNPs were synthesized as previously described (Kassem et al 2015). After that, surface functionalization was performed by silanizing YNPs with 3-trimethoxysilylpropyl methacrylate and grafting an ethylene glycol methacrylate phosphate (EGMP) co-polymer, as described in Sayour et al (2019) in addition to N-Fluorescein Acrylamide which was added in polymerization mixture as fluorescent monomer (Tan et al 1992).…”
Section: Synthesis Of Functionalized Core-shell Yttrium Oxide Nanopar...mentioning
confidence: 99%
“…In previous work, ultrafine YNPs were prepared and the surface modification was achieved by grafting a copolymer made of poly EGMP to improve the biocompatibility and enhance biodistribution of YNPs with dose up to 0.1 mg/g bwt in normal 1-month-old Sprague-Dawley rats and pointed to the ability of NPs to distribute successfully to the brain shortly after tail vein injection without toxicity. Also, we approved that functionalized core-shell YNPs possess powerful antioxidant activity after one dose injection of 0.2 mg in a heat-stressed rat model but further research is needed to give answers on the dose-dependent antioxidant efficacy of YNPs with rescuing the oxidative stress-induced degenerative disorders in different organs especially the brain (Kassem et al 2015(Kassem et al , 2020Sayour et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, yttrium oxide nanoparticles were used to improve or alleviate cognitive impairments caused by cholestasis. The results showed that intraperitoneal injection of yttrium oxide nanoparticles from one day after surgery for 21 days increased the ability to acquire and recall memory and increased the expression of genes involved in mitochondrial biogenesis in cholestatic rats (Buzea et al, 2007, Kassem et al, 2015. Yttrium oxide nanoparticles can cross the blood-brain barrier and protect cells against free radicals and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…These particles have wide diagnostic and therapeutic applications. Several studies have shown that nanoparticles, due to their antioxidant properties, can protect cells against oxidative stress, the production of free radicals, and neural damage (Buzea et al, 2007;Kassem et al, 2015). Nanoparticles also increase the synaptic exibility of brain hippocampal neurons, and by blocking NMDA-dependent pathways, they increase magnesium concentrations in the brain cell spaces, thereby improving memory.…”
Section: Introductionmentioning
confidence: 99%